A Mini Review on Covid-19 Infection and Severe Outcome on Cancer Patient - Sameer Badri Al-Mhanna; Zaidi Zakara; Hafeez Abiola Afolabi; Afolabi-Owolabi Oluwafunke Toyin; Rashidat Folashade Elesho (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction December 2019, the world witness a new strand of pathogen known as coronavirus-2 (SARSCoV-2), later recognized as the novel coronavirus disease (COVID-19). By April 1st 2020, the confirmedcases were over 800,000 around the world with over 40,000 fatalities. Individuals with cancer are morevulnerable to COVID-19 impact because of compromised health-status.Methods A comprehensive search method was applied by searching the google scholar using the keywordsto select eligible studies to be included in the reviewResults The findings showed that patients with cancer, especially thoracic malignancies that wereinfected with COVID-19 infection during the hospital stay developed severe cardiorespiratory symptomsthat warranted use of a mechanical ventilator. The cancer patients with COVID-19 had increased rateof hospitalization and a poor outcome as well as a higher risk of mortality when compared to healthyindividuals. It is recommended that cancer patients taking anti-tumour drugs should undergo early screeningfor COVID-19 because the anti-tumour drugs also suppress the immune system. Hence, their dosage shouldbe regulated appropriately incase of COVID-19 co-infection.Conclusion In risk-mitigation pandemic scenario in COVID-19 period, efforts should be made not tocompromise the prognosis of cancer in these patients by adhering to treatment guideline.